Optimism and Hope in Chronic Disease: A Systematic Review - Schiavon, Cecilia C.; Marchetti, Eduarda; Gurgel, Léia G.; Busnello, Fernanda M.; Reppold, Caroline T. (Frontiers in Psychology, 2017)
There is a growing recognition that positive psychological functioning (which includes constructs such as optimism and hope) influences health. However, the understanding of these underlying mechanisms in relation to health is limited. Therefore, this review sought to identify what the scientific literature says about the influence of optimism and hope on chronic disease treatment. A search was conducted in the PsycINFO, Scopus, Pubmed and Web of Science databases using the indexing terms optimism, hope, chronic diseases, randomized controlled trial and treatment between 1998 and 2015. In the articles, we identified the most studied diseases in context, the assessment instruments used, the participant characteristics investigated, the results found and the publication dates. From our analysis of the articles that met our inclusion criteria, it appears that the study of these constructs is recent and there is evidence that individuals with greater optimism and hope seek to engage in healthier behaviors, regardless of their clinical status, and that this contributes to chronic disease treatment. More research is needed so that targeted interventions can be carried out effectively in chronic disease treatment.